1 Corinthians: an exegetical and contextual commentary - Spurgeon, Andrew B. (India commentary on the New Testament, 2017)
The India Commentary on the New Testament (ICNT) series aims to give a well-informed exposition of the meaning of the text and relevant reflections in everyday language from a contemporary Indian context. The intended audience is the theological seminary or bible college, both students and faculty. The commentaries are also ideal for pastors and lay people with an interest in theology or responsibilities for preaching in the local congregation. The commentaries are culturally rooted, and the various applications relating to culture, society, and religious life will help those involved with cross-cultural evangelism and mission work. There is no direct equivalent to the ICNT, and hence, this is the first Indian commentary serving India, the entire subcontinent-India, Nepal, Bangladesh, and Sri Lanka. - back cover